APLIKASI THEORY OF PLANNED BEHAVIOR DALAM MEMBANGKITKAN NIAT BERWIRAUSAHA BAGI MAHASISWA FAKULTAS EKONOMI UNPAZ, DILI TIMOR LESTE - Cruz, Leonel da; Suprapti, Sri; Yasa, Kerti (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
This study aims to determine the effect of applications in the theory of planned behavior evokes entrepreneurship intentions. This study was done to help the Faculty of Economics, University of da Paz in East Timor as the basis for a decision application theory of planned behavior and also to contribute to science in terms of entrepreneurship. The population in this study were students who graduated from the course Entrepreneurship program. Techniques in determining the members of the sample using proportionate stratified random sampling technique. Sample size determination based on the formula of Taro Yamane is a sample of 94 people with a number of indicators of research as many as 12 were all tertuan in the form of a statement on the questionnaire. Data analysis method used is multiple linear regression analysis. The results showed that partially where the independent variable X2 is the dominant variable influence on the intention of entrepreneurship, with a beta value of 0.342 and variables occupy the second position is the behavior of the control variables (X3), where in the beta value of 0.276 and ranks third and has The smallest effect is the attitude with value beta of 0.218. Feasibility analysis models indicate R2 value of 0,604, which may mean that 60.4 percent of the variation or the merits of Intention to entrepreneurship can be explained Attitude (X1) subjective norm (X2) and control the behavior X3 together, while the remaining 39.6 percent is explained by other variables not analyzed in this study. The implications of the research that can be raised is increasingly understand the application, the theory of planned behavior intention of increasing entrepreneurship by students of the Faculty of Economics. Therefore, the Faculty of Economics is expected to be able to improve the attitude, subjective norm, and control the behavior of students, and also must expand the department that focuses on entrepreneurship so as to generate entrepreneurial intentions.
Keywords: Attitudes, Subjective Norms, Control Behavior, and Intention